Multiresistant ST59-SCCmec IV-t437 clone with strong biofilm-forming capacity was identified predominantly in MRSA isolated from Chinese children. Issue 1 (December 2017) - Yang, Xin; Qian, Suyun; Yao, Kaihu; Wang, Lijuan; Liu, Yingchao; Dong, Fang; Song, Wenqi; Zhen, Jinghui; Zhou, Wei; Xu, Hong; Zheng, Hongyan; Li, Wenting
Abstract Background This study aimed to investigate the clinical and molecular epidemiology and biofilm formation ofStaphylococcus aureus (SA) isolated from pediatricians in China. Methods SA strains were isolated from Beijing Children's hospital from February 2016 to January 2017. Isolates were typed by multilocus sequence typing (MLST), spa and SCCmec typing (for Methicillin-resistant SA [MRSA] only). Antimicrobial susceptibility testing was performed by agar dilution method except sulphamethoxazole/trimethoprim (E-test method). Biofilm formation and biofilm associated genes were detected. Results Totally 104 children (41 females and 63 males; median age, 5.2 months) were enrolled in this study, in which 60 patients suffered from MRSA infection. Among the 104 cases, 54.8% were categorized as community associated SA (CA-SA) infections. The children under 3 years were more likely to occur CA-SA infections compared with older ones (P = 0.0131). ST59-SCCmec IV-t437 (61.7%) was the most prevalent genotype of MRSA, and ST22-t309 (18.2%), ST5-t002 (9.1%), ST6-t701 (9.1%), ST188-t189 (9.1%) were the top four genotypes of methicillin-sensitive SA (MSSA). All the present isolates were susceptible to linezolid, vancomycin, trimethoprim-sulfamethoxazole, mupirocin, tigecyclin, fusidic acid. No erythromycin-susceptible isolate was determined, and only a few isolates (3.8%) were identified as susceptible to penicillin. Multi-drug resistant isolates were reponsible for 83.8% of the ST59-SCCmec IV-t437 isolates. The isolates with strong biofilm formation were found in 85% of MRSA and 53.2% of MSSA, and in 88.7% of ST59-SCCmec IV-t437 isolates. Biofilm formation ability varied not only between MRSA and MSSA (P = 0.0053), but also greatly among different genotypes (P < 0.0001). The prevalence of the biofilm associated genes among ST59-SCCmec IV-t437 clone was:icaA (100.0%), icaD (97.3%), fnbpA (100.0%), fnbpB (0), clfA (100%), clfB (100%), cna (2.7%), bbp (0), ebpS (88.5%), sdrC (78.4%), sdrD (5.4%), andsdrE (94.5%). Conclusions These results indicated strong homology of the MRSA stains isolated from Chinese children, which was caused by spread of multiresistant ST59-SCCmec IV-t437 clone with strong biofilm formation ability. The MSSA strains, in contrast, were very heterogeneity, half of which could produce biofilm strongly.